Superficial Circumflex Iliac Artery Perforator Flap with Bilobed Design for the Donor Defect after Wrap‐Around Flap Transfer Reconstruction - Chaotao Hu; Biao Hou; Xiongjie Huang; Yunhua Xu; Qiang He; Jiangang Song; Songlin Xie (Orthopaedic Surgery, 2023)
Objective The repair of great toe donor site defect after wrap‐around flap transfer is still controversial. The bilobed superficial circumflex iliac artery perforator (SCIP) flap can improve the aesthetics of the great toe while maintaining its function. Thus, this study aimed to report our experience in the reconstruction of big toe donor site defects with the bilobed SCIP flap and describe the clinical outcomes. Methods This study was a retrospective trial. From May 2017 to May 2020, 13 patients with the great toe donor site defect after wrap‐around flap transfer were included in this study. The average age of the patients was 44 years (range, 23–60 years). All patients received free bilobed SCIP flaps to reconstruct the donor site defect of the great toe. Relevant clinical features were recorded preoperatively. The thickness and design of the SCIP flap and the harvesting layer of the flap were measured during the operation. The survival rate of flaps and skin grafts and the incidence of infection were recorded after operation. At follow‐up, donor site complications and postoperative outcomes were evaluated. Results In all cases, the SCIP flap covering the donor site of the great toe survived. All patients were followed up for 24–40 months (mean, 30.5 months). The average thickness of the SCIP flap was 0.38cm. All SCIP flaps were harvested from the superficial fascial layer except for three obese patients. The thin SCIP flap had a bilobed design with no further defatting procedures. Postoperatively, the great toe‐nail flap donor site regained its original appearance without bloating or flap necrosis. There was a hidden linear scar in the groin donor site, which did not affect hip joint movement. All patients were satisfied with the aesthetics of the surgical site. Conclusion The SCIP flap with bilobed design for repairing the donor defect of the great toe after wrap‐around flap transfer is a kind of surgical method with excellent contour, meeting the requirements of function and aesthetics.